2022
DOI: 10.3389/fmars.2022.847032
|View full text |Cite
|
Sign up to set email alerts
|

Blue Whale Body Condition Assessed Over a 14-Year Period in the NE Pacific: Annual Variation and Connection to Measures of Ocean Productivity

Abstract: Large marine mammals can serve as an indicator of the overall state of the environment due to their apex position in marine food webs and their functions as sentinels of change. Reductions in prey, driven by changes in environmental conditions can manifest in reduced fat stores that are visible on whales. We developed a non-invasive technique using photographs of blue whales taken on the US west coast from 2005-2018 (n=3,660) and scored body condition based on visible undulations from the vertebral processes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…While inhabiting the CalCOFI region they forage exclusively on krill, preferring Thysanoessa spinifera to North Pacific krill (Nickels et al, 2019). Due to their specialized foraging preferences, blue whale encounter rates may be an indicator of local productivity (Wachtendonk et al, 2022). In the summer of 2021, encounter rates of blue whales were the highest throughout the timeseries (Supplementary Appendix).…”
Section: At Sea Birds and Mammalsmentioning
confidence: 99%
“…While inhabiting the CalCOFI region they forage exclusively on krill, preferring Thysanoessa spinifera to North Pacific krill (Nickels et al, 2019). Due to their specialized foraging preferences, blue whale encounter rates may be an indicator of local productivity (Wachtendonk et al, 2022). In the summer of 2021, encounter rates of blue whales were the highest throughout the timeseries (Supplementary Appendix).…”
Section: At Sea Birds and Mammalsmentioning
confidence: 99%
“…There may be several reasons as to why there is a difference in BC between the west and east coast populations, including temporal variation. Baleen whales showed fluctuations in BC among years of varying environmental conditions (Lockyer 1986;Vikingsson et al 2013;Soledade Lemos et al 2020;Wachtendonk et al 2022), with the potential for this change to be extreme (Coughran et al 2023). This may lead to different amounts of acquired energy among different feeding seasons and, in turn, a poorer or better BC at the time of sampling.…”
Section: Body Condition Comparison Between West and East Coast Popula...mentioning
confidence: 99%
“…In contrast to strict capital breeders that may fast for months on the wintering/breeding grounds (i.e., southern right whales, Eubalaena australis, Carroll et al, 2021), blue whales likely fast for short periods of time while transiting between summer and winter foraging grounds (Bailey et al, 2009). This strategy makes blue whales particularly vulnerable to changes in resource availability because of their high energetic requirements (Acevedo-Gutieŕrez et al, 2002), and whales in poor body condition are frequently observed during years characterized by low primary productivity (Casillas-López, 2016;Wachtendonk et al, 2022). Studies that address individual migratory and dietary strategies of this species are needed to better understand habitat use, and how this varies among age and sex categories, which in turn would provide information on population dynamics that are critical to their management and conservation.…”
Section: Introductionmentioning
confidence: 99%